(untitled) (Khairulummah, 2022)
In this Article, The scholar intended to bring to light the cream of folk Literature of “Allegorical attribution(الاسناد المجازي) in the Qur’an discourse and its rhetorical purposes” by prescription and description of its properties and features. The Method followed in this research is " Rhetorical , Descriptive and Analytical Study" The Research is actually an investigated of Stylistic Features of Allegorical attribution . It will inspire readers to get recreated from the World best academic Treasury of Proverbs and Aphorisms having diversified forms. Moreover this Research will also appeal the Scholars who want to make further research in the Stylistic Study of Allegorical attribution. As per our research, we studied all kinds of psychical Metaphor and I explained it with examples in the light of authentic books of rhetoric written by Islamic scholars.